Q. 4

# In any triangle ABC, prove the following:

Answer :

Let a, b, c be the sides of any triangle ABC. Then by applying the sine rule, we get

⇒a = k sin A

Similarly, b = k sin B

So, a - b = k(sin A - sin B)

And a + b = k(sin A + sin B)

So, the given LHS becomes,

But,

Substituting the above values in equation (i), we get

Rearranging the above equation we get,

Hence proved

Rate this question :

In any triangle ABC, prove the following:

RD Sharma - Mathematics

In any triangle ABC, prove the following:

a cos A + b cos B + c cos C = 2b sin A sin C = 2c sin A sin B

RD Sharma - MathematicsIn any triangle ABC, prove the following:

a(sin B – sin C) + b(sin C – sin A) + c(sin A – sin B) = 0

RD Sharma - MathematicsIn any triangle ABC, prove the following:

RD Sharma - Mathematics

In any triangle ABC, prove the following:

a^{2} sin (B – C) = (b^{2} – c^{2}) sin A

In any triangle ABC, prove the following:

RD Sharma - Mathematics

In any triangle ABC, prove the following:

b cos B + c cos C = a cos (B – C)

RD Sharma - MathematicsIn any triangle ABC, prove the following:

a^{2} (cos^{2} B – cos^{2} C) + b^{2} (cos^{2} C – cos^{2} A) + c^{2} (cos^{2} A – cos^{2} B) = 0

In a ∆ABC, if sin^{2} A + sin^{2} B = sin^{2} C, show that the triangle is right angled.